2019
DOI: 10.3390/joitmc5030058
|View full text |Cite
|
Sign up to set email alerts
|

Are Black Friday Deals Worth It? Mining Twitter Users’ Sentiment and Behavior Response

Abstract: The Black Friday event has become a global opportunity for marketing and companies’ strategies aimed at increasing sales. The present study aims to understand consumer behavior through the analysis of user-generated content (UGC) on social media with respect to the Black Friday 2018 offers published by the 23 largest technology companies in Spain. To this end, we analyzed Twitter-based UGC about companies’ offers using a three-step data text mining process. First, a Latent Dirichlet Allocation Model (LDA) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 53 publications
(85 reference statements)
2
37
0
2
Order By: Relevance
“…First, in terms of purchase intention predictors, the present empirical results yielded from the 1377 sampling data demonstrated that, flow, as an intrinsically enjoyable and favorable experience that attracts users to frequently use their preferred brand, imposes strong predictions for future purchase intention. This finding expanded the research topic dealing with the application of flow theory into marketing and business, as it also confirmed the few already known previous findings [6,67,103]. This study also found that brand image directly and positively affects consumers' purchase intention.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, in terms of purchase intention predictors, the present empirical results yielded from the 1377 sampling data demonstrated that, flow, as an intrinsically enjoyable and favorable experience that attracts users to frequently use their preferred brand, imposes strong predictions for future purchase intention. This finding expanded the research topic dealing with the application of flow theory into marketing and business, as it also confirmed the few already known previous findings [6,67,103]. This study also found that brand image directly and positively affects consumers' purchase intention.…”
Section: Discussionsupporting
confidence: 89%
“…This result set is very coherent with the literature, emphasizing how the contemporary economy is more and more detached from a mere image era, and is instead more attached with a reputation and identity era, this is an era where not only appearance features are crucial, but also behavioral and pragmatic features of companies and brands [103], as the features capable of building a company and brand reputation and to deploy its identity in relation to its stakeholders, including its customers [105]. Our results show therefore that, within such a scenario, the consumer adoption of a pervasive product such as the smartphone is based only slightly on its appearance features, its brand image, which still has some significant direct effect, being rather much more grounded in the relationship the smartphone is capable to build with its customers.…”
Section: Discussionsupporting
confidence: 81%
“…Our decision to omit emoticons in our analysis was based on the fact that the analysis techniques used in the present study were not meant for the analysis of graphics or graphic icons and were associated with the analysis of feelings in NLP datasets [38]. This filtering process resulted in a final sample of n = 9801 total tweets with direct relevance to the education sector [2,36,37].…”
Section: Data Sampling Extraction and Collectionmentioning
confidence: 99%
“…Finally, the results are given meaning by applying data mining techniques and a data visualization algorithm for complex networks, developed by Blondel et al [36] and known as modularity report (MR). This uses the open source software Gephi, with which different image resolutions are applied to visualize and identify communities in the sample as they relate to education innovation [37]. Then, the results of the discovered topics are compared with UGC communities on Twitter concerned with innovation in education.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, with the emergence and development of web 2.0, traditional business reputation, or offline reputation, as explained above, is considered obsolete, or evolving and coexisting with online reputation [31,32].…”
Section: Corporate Reputation and Online Reputationmentioning
confidence: 99%